Gender and Climate Services in Vietnam - Turner, Jacquelyn (2019)
The International Day of Rural Women (IDRW) celebrates the vital role that rural women play in the well-being and development of their communities. When it comes to agriculture and climate change, the specific needs of women are often overlooked when developing farming practices and technologies to adapt to a changing climate.